Genetic and morphological studies of Trichosirocalus species introduced to North America, Australia and New Zealand for the biological control of thistles. Issue 1 (9th November 2015) - De Biase, A.; Colonnelli, E.; Belvedere, S.; La Marca, A.; Cristofaro, M.; Smith, L.
Abstract: Trichosirocalus horridus sensu lato has been used as a biological control agent of several invasive thistles ( Carduus spp., Cirsium spp. and Onopordum spp.) since 1974. It has been recognized as a single species until 2002, when it was split into three species based on morphological characters: T. horridus, Trichosirocalus briesei and Trichosirocalus mortadelo, each purported to have different host plants. Because of this taxonomic change, uncertainty exists as to which species were released in various countries; furthermore, there appears to be some exceptions to the purported host plants of some of these species. To resolve these questions, we conducted an integrative taxonomic study of the T. horridus species complex using molecular genetic and morphological analyses of specimens from three continents. Both mitochondrial cytochrome c oxidase subunit I and nuclear elongation factor 1α markers clearly indicate that there are only two distinct species, T. horridus and T. briesei . Molecular evidence, morphological analysis and host plant associations support the synonymy of T. horridus (Panzer, 1801) and T. mortadelo Alonso-Zarazaga & Sánchez-Ruiz, 2002. We determine that T. horridus has been established in Canada, USA, New Zealand and Australia and that T. briesei is established in Australia. The former species was collected from Carduus, Cirsium and Onopordum spp. in the field, whereas the latter appears to be specific to Onopordum .